An aborted rift process of Aptian-Albian age in central Peru, and its significance for the margin geodynamics - Romero Fernández, Darwin (2005)
Early studies between 1924 and 1970 in the Peruvian Central Andes described a volcano-sedimentary sequence to the top of Goyllarisquizga Group, in some cases including it in this group. ln the last 30 years, works in Central Peru referring to the Cretaceous (e.g. Chayllacatana Formation) do not give importance to these volcanosedimentary deposits. Recently Romero et al., 2004 developed the first geodynamics interpretations of these sediments assumed the sedimentation during Lower Albi an in the Central Peru. Other works in south Peru mentioned volcanp-sedirnentary deposits in the Matalaque Formation but they do not give a basin geodynamic interpretation. This work tries to understand the geodynamics of the Peruvian continental margin during the Aptian-Albian, for it we focused in the study of Chayllacatana and Matalaque basins.